Response to thyrotrophin-releasing hormone in atrial dysrhythmias. Issue 636 (October 1978) - Symons, C.; Myers, A.; Kingstone, D.; Boss, M.
Abstract : Seventy-eight clinically euthyroid patients with atrial dysrhythmias, either established or paroxysmal, and sixty-three patients in sinus rhythm with coronary disease were screened for hyperthyroidism using thyroid function tests including the thyroid-stimulating hormone (TSH) response to thyrotrophin-releasing hormone (TRH). All had normal levels of serum thyroxine (T4) apart from three with dysrhythmias who were found to have hyperthyroidism. Twenty per cent of patients with atrial dysrhythmias and 10% of those in sinus rhythm had exaggerated TSH response to TRH. Thirty-six per cent of patients with an exaggerated response of TSH to TRH had significant titres of thyroid auto-antibodies compared with 15% with positive antibodies in those with normal TSH response to TRH. Auto-immune thyroid disease may be more closely related to heart disease than has previously been recognized. Rapid atrial dysrhythmias may occur in the presence of a normal serum thyroxine, high levels of TSH and positive thyroid antibodies.